2020
DOI: 10.1111/sji.12891
|View full text |Cite
|
Sign up to set email alerts
|

The use of aluminium hydroxide as adjuvant modulates the specific antibody response—A Brown Norway rat study with native and denatured cow's milk allergens

Abstract: There is a need for efficient methods to treat food allergy; however, no immunotherapeutic method has yet been satisfactory due to the high rate of unpredictable severe reactions and the limited efficacy. Therefore, modified versions of food allergens have been suggested as alternatives to the parent proteins for immunotherapy. The aim of the study was to compare the inherent allergenicity of the native and denatured version of the cow's milk proteins β‐lactoglobulin and α‐lactalbumin, and to study the impact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…In all groups, the IgE responses to both N-OVA and D-OVA were inconsistent, although more robust against N-OVA. In line with these findings, Bøgh et al reported that after IP administration, native and denatured cow’s milk allergens (β-lactoglobulin and α-lactalbumin) triggered different sensitizing capacities, with native allergens sensitizing more effectively than denatured ones [ 17 ]. These results, and the ones reported in the present study, suggest that mice can be IP sensitized to different structural forms of food allergens, and this fact should be considered in the search for an animal model to evaluate the allergenic potential of processed foods.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In all groups, the IgE responses to both N-OVA and D-OVA were inconsistent, although more robust against N-OVA. In line with these findings, Bøgh et al reported that after IP administration, native and denatured cow’s milk allergens (β-lactoglobulin and α-lactalbumin) triggered different sensitizing capacities, with native allergens sensitizing more effectively than denatured ones [ 17 ]. These results, and the ones reported in the present study, suggest that mice can be IP sensitized to different structural forms of food allergens, and this fact should be considered in the search for an animal model to evaluate the allergenic potential of processed foods.…”
Section: Discussionmentioning
confidence: 86%
“…Furthermore, it should be highlighted that undetectable IgE levels using ELISA do not mean the absence of sensitization, as in our experience, serum levels of biological markers of an allergic immune response can become evident after an intragastric challenge [ 10 ]. In the present study, we used Al(OH) 3 (Imject Alum) for OVA-sensitization, a systemic adjuvant that enhances the production of both IgG and IgE antibodies [ 17 , 18 ], which can compete for the same OVA epitopes [ 19 ]. In fact, a high ratio of IgG/IgE in serum after IP sensitizations [ 20 , 21 ] as well as the convenience of depleting IgG to accurately assess IgE in serum [ 11 ] were documented.…”
Section: Discussionmentioning
confidence: 99%
“…The experimental modeling scheme was based on Abril-Gil et al, [23] Madsen et al, [24] and Bøgh et al [25][26][27] with slight modifications. On days 1, 3, and 5 of the experiment, 500 μL saline or 500 μL saline containing 2 mg PP, MP, or SP including 125 μL Imject Alum (40 mg mL −1 , Thermo Fisher Scientific Inc., USA) was injected intraperitoneally into each rat for sensitization.…”
Section: Dosage Informationmentioning
confidence: 99%